Factors which aid or inhibit peer-to-peer interaction during Project Based Learning in a virtual high school for anxious school refusers: a case study in the United Kingdom - Royston-Muirhead, Lee (School of Education, 2017)
The prevalence of adolescent school absenteeism due to severe bullying in the UK exceeds 16 000 young people, and the occurrence of anxious school refusers (including self-exclusion due to bullying) is a well-documented issue that transcends geographical borders. The research context for this study is a virtual school (Red Balloon of the Air) that provides educational, therapeutic and social support for some of these young people who are missing out on an education, many of whom have had difficult experiences with peers in previous educational settings. The aim of this case study was to investigate factors that aid or inhibit peer-to-peer interaction and collaboration during a Project Based Learning (PBL) activity in a virtual high school for anxious school refusers. A conceptual framework drawing on the works of Moore (1989), Curtis and Lawson (2001) and Murphy (2004) was developed to analyse the subsidiary research questions. The findings show that notable levels of peer-to-peer interaction were recorded in the chat transcripts from the PBL activity (31.9%), however this interaction did not constitute any notable form of collaboration in the small group activities where the highest concentration of peer-to-peer interactions were recorded. The factors that appear to aid peer-to-peer interaction include incorporating small group work, pairing newer students with more experienced students, and introducing blended learning opportunities whereby students interact face-to-face. In addition to this, on average an increased length of time at the virtual school seems to increase peerto- peer interaction, with the exception of students experiencing emotional difficulty during activities, and level of student choice resulting in students sometimes choosing to working alone. The role of the teacher in peer-to-peer interactions and supporting collaboration is a prominent theme, in particular how the use of technology increases the teacher's access to student conversations which could make the teachers more likely to intervene with solutions. Peer-to-peer interaction and social presence are a pre-requisite for collaboration, however as evidenced in this study the presence of both does not automatically mean collaboration will occur. The limitations of this study include that the findings are based on one PBL activity, which took place in the final weeks of the academic year with no links to the national curriculum. The findings of the study serve as a foundation for further research in the field.